2009
DOI: 10.1038/aps.2009.138
|View full text |Cite
|
Sign up to set email alerts
|

SM905, an artemisinin derivative, inhibited NO and pro-inflammatory cytokine production by suppressing MAPK and NF-κB pathways in RAW 264.7 macrophages

Abstract: Aim: To elucidate the anti-inflammatory potentials and underlying mechanisms of SM905, a novel artemisinin derivative, in lipopolysaccharide (LPS)-stimulated murine macrophage RAW 264.7 cells. Methods: Nitric oxide (NO) generation, cytokine production, and the protein expression levels of inducible nitric-oxide synthase (iNOS) and cyclooxygenase-2 (COX-2) were examined using a Griess assay, an enzyme-linked immunosorbent assay (ELISA) and a Western blotting assay, respectively. The mRNA expression was measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(34 citation statements)
references
References 36 publications
2
32
0
Order By: Relevance
“…However, most artemisinin derivatives possess poor water solubility or low bioavailability, which limits their further applications to treat autoimmune diseases. Several series of new artemisinin derivatives have been synthesized, and the water-soluble artemisinin derivative SM934 showed higher bioavailability, better bioactivity, and lower toxicity (25)(26)(27)(28). The acute toxicity of SM934 was tested in mice, and the median lethal dose was ϳ2 gm/kg.…”
mentioning
confidence: 99%
“…However, most artemisinin derivatives possess poor water solubility or low bioavailability, which limits their further applications to treat autoimmune diseases. Several series of new artemisinin derivatives have been synthesized, and the water-soluble artemisinin derivative SM934 showed higher bioavailability, better bioactivity, and lower toxicity (25)(26)(27)(28). The acute toxicity of SM934 was tested in mice, and the median lethal dose was ϳ2 gm/kg.…”
mentioning
confidence: 99%
“…At last, SM 735, SM 905, SM 933, and SM 934 ( Figure 2) were selected and tested in the animal models for 2,4-dinitrofluorobenzene (DNFB)-induced delayed-type hypersensitivity (DTH) reaction, sheep red blood cell (SRBC)-induced antibody production, and experimental autoimmune encephalomyelitis (EAE). Up to date, a number of papers related their immuno-suppressive activity and possible mechanisms have been published mainly from this Institute [55][56][57][58][59][60][61][62][63][64] . The preclinical research of SM 934 is in progress.…”
mentioning
confidence: 99%
“…Since multiple studies have shown that LPS-induced expression of pro-inflammatory mediators such as iNOS, COX-2, IL-1b and IL-6 are regulated by NF-jB and MAPKs signaling pathways [3,37], we examined whether MHNA affected NF-jB and MAPKs signaling pathways activation. We found that MHNA inhibited the LPSinduced increases in NF-jB DNA-binding activity and NFjB transcriptional activity in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages, as major cells in inflammation, play an important role in the pathogenesis of inflammation by secreting various inflammatory mediators such as nitric oxide (NO), prostaglandin E 2 (PGE 2 ), tumor necrosis factor alpha (TNF-a), interleukin-1 (IL-1) and interleukin-6 (IL-6) [1][2][3]. When these mediators are overproduced, they cause an excessive inflammatory response, leading to the occurrence of inflammatory diseases [4][5][6].…”
Section: Introductionmentioning
confidence: 99%